the fellowship of the ring : being the first part of the lord of the rings - Tolkein , J.R.R; J.R.R Tolkein (New York Houghton Mifflin company, 1954)
The Fellowship of the Ring (1954), the first volume of J.R.R. Tolkien$1 (Bs The Lord of the Rings, follows hobbit Frodo Baggins as he inherits the dangerous One Ring from Bilbo Baggins. Advised by Gandalf, Frodo flees the Shire with his companions to prevent the Dark Lord Sauron from retrieving the ring, leading to a perilous journey toward Rivendell. s